Mediating role of organizational justice in relationship between Islamic work ethics and employee turnover intention - Faisal Durrani; Kashif ur Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
The prime concern of this study is to probe the relationship between Islamic work ethics (IWE) and employee turnover intention (TI) with the mediation of organizational justice (OJ). Studying this relationship is significantly new in the corporate sector of Pakistan. A sample of 550 employees from the corporate sector of Pakistan was carried out. The results accumulated from the study indicated that Islamic work ethics can play a vital role in the development and progress of organizations as a remedy for modern organizational, social and cultural issues in corporate sector of Pakistan. A questionnaire containing 40 items was adopted. Middle and senior management staff of 32 corporate sector organizations from 10 cities of Pakistan are taken as participants. The results showed that the Islamic work ethics and turnover intention are negatively associated. The mediating effect of overall organizational justice has shown positive mediation between Islamic work ethics and turnover intention. The study concluded that the idea of IWE works as a remedy for the growing ethical crisis of corporate sector organizations of Pakistan which should be infused in organizational culture for sustainable organizational performance and growth.
Keywords: 330; Islamic work ethics; organizational justice; turnover intention; organizational distributive justice; organizational procedural justice; organizational interactional justice